Analisis Kesalahan Siswa dalam Penyelesaian Soal Kaidah Pencacahan - Wachid Nugroho (ARITMATIKA: Jurnal Riset Pendidikan Matematika, 2021)
This study aims to identify, explore, sort and categorize the types of student errors of class XII MATIQ As-Surkati Salatiga in solving counting rules questions on the sub-material filling slots, permutations, and combinations. The results of identification of various student errors are used to investigate and determine the factors that cause student errors so that the learning process can be improved. This study uses a descriptive research method with a qualitative approach. The research was conducted at madrasah Tahfidzul Quran As-Surkati by taking 28 students of class XII as the subject for all analysis. The data collection method used documentation study on the result of student’ written test correction on daily assessments and researcher observations as the main instrument with confirmation of the validity of the data through unstructered interviews. The stages of data analysis are as follows, 1) collecting data in the form of daily assessment results for all students, 2) correcting the work results of all students, 3) identifying the types of student work errors, and 4) grouping the types of student work errors. Researchers observed from the time the learning of the counting rules took place to daily assessments. The technique of determining the informants of the respondents who are shown the results of their work uses the criterion sampling method which aims to obtain informants (work results) that match the specified criteria (types of student errors).The results showed that the categories of student error types were misunderstanding of the concept (40%), error in interpreting questions (35%), error in procedures (20%), and error in algebraic operations (5%). Meanwhile, the factors that cause students' errors are, first, difficulty understanding the questions due to the low level of understanding of the concept and the high complexity of the material. The second cause of student error is difficulty in learning the material due to lack of focus when studying, the large amount of learning load, feeling that there is less time to study, and low learning motivation.